2020
DOI: 10.1371/journal.pntd.0007952
|View full text |Cite
|
Sign up to set email alerts
|

Utility of primary cells to examine NPC1 receptor expression in Mops condylurus, a potential Ebola virus reservoir

Abstract: The significance of the integral membrane protein Niemann-Pick C1 (NPC1) in the ebolavirus entry process has been determined using various cell lines derived from humans, nonhuman primates and fruit bats. Fruit bats have long been purported as the potential reservoir host for ebolaviruses, however several studies provide evidence that Mops condylurus, an insectivorous microbat, is also an ebolavirus reservoir. NPC1 receptor expression in the context of ebolavirus replication in microbat cells remains unstudied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…We compared antiviral activity following U18666A treatment and NPC1 deficiency and demonstrated that NPC1 inhibition offers a protective function against viral infection, suggesting the essential role of NPC1 in the replication of a wide range of enveloped viruses. NPC1, an essential protein involved in cholesterol delivery from the lysosomal lumen to the membrane, is highly conserved and ubiquitously expressed among mammalian cells (Bokelmann et al, 2020). A previous report demonstrated that an Ebola virus surface glycoprotein binds to luminal loop 2 of NPC1, which serves as a passive attachment site for downstream cellular infection (Miller et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We compared antiviral activity following U18666A treatment and NPC1 deficiency and demonstrated that NPC1 inhibition offers a protective function against viral infection, suggesting the essential role of NPC1 in the replication of a wide range of enveloped viruses. NPC1, an essential protein involved in cholesterol delivery from the lysosomal lumen to the membrane, is highly conserved and ubiquitously expressed among mammalian cells (Bokelmann et al, 2020). A previous report demonstrated that an Ebola virus surface glycoprotein binds to luminal loop 2 of NPC1, which serves as a passive attachment site for downstream cellular infection (Miller et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, it is conceivable that S142 may represent an adaptation of BOMV to M. condylurus NPC1. It has previously been suggested that each ebolavirus is adapted to a specific bat host [ 62 ], with variation occurring across the NPC1 binding domain, although a partial M. condylurus NPC1 sequence shows F504 is conserved [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, NPC1 was shown to be a genetic determinant of filovirus susceptibility in bat cells; NPC1 polymorphisms found in specific bat species result in reduced interactions between filoviruses and NPC1, influencing the cellular susceptibility of bats to filovirus infection, replication, and virulence [34]. In culture, M. condylurus cells typically have low NPC1 expression levels compared to cells from highly symptomatic hosts, such as humans [35]. Infection of M. condylurus cells with EBOV revealed a potential correlation between NPC1 receptor expression level and virus replication rate [35].…”
Section: Introductionmentioning
confidence: 99%
“…In culture, M. condylurus cells typically have low NPC1 expression levels compared to cells from highly symptomatic hosts, such as humans [35]. Infection of M. condylurus cells with EBOV revealed a potential correlation between NPC1 receptor expression level and virus replication rate [35].…”
Section: Introductionmentioning
confidence: 99%